Impact of relative systemic hypertension on the heart in sickle cell anaemia - Opeyemi O. Oni; Adewole A. Adebiyi; Akinyemi Aje; Titilola S. Akingbola (Indian Heart Journal, 2020)
Sickle cell anaemia (SCA) is associated with macrovascular complications at relatively normal blood pressures. This has led to the development of the term ‘relative systemic hypertension’ (RSH). The electrocardiography (ECG) and echocardiography (ECHO) findings in these people has not been well highlighted.Patients with SCA in steady state were consecutively recruited. History, physical examination, ECG and ECHO information were obtained from all participants after informed consent was obtained. Eighty-three people were recruited in all- 15 of which had RSH, giving a prevalence of 18.1%. Those with RSH had higher packed cell volumes (PCV), smaller right atria area, lower tricuspid regurgitant velocities, lower incidence of early satiety, longer QTc and higher frequency of a history of vaso-occlusive crises. The indices of right and left ventricular function were normal in both groups. Right atrial area was the only significant determinant of RSH in this study.RSH is associated with higher PCV, longer QTc and smaller right atrial area in SCA patients. More studies to evaluate sympathetic output in SCA with RSH is required.